No benefit of ingestion of a ketone monoester supplement on 10-km running performance - Evans, M.; McSwiney, F. T.; Brady, A. J.; Egan, B. (Medicine & Science in Sports & Exercise, 2019)
Preexercise ingestion of exogenous ketones alters the metabolic response to exercise, but effects on exercise performance have been equivocal. Methods On two occasions in a double-blind, randomized crossover design, eight endurance-trained runners performed 1 h of submaximal exercise at approximately 65% V.O2max immediately followed by a 10-km self-paced time trial (TT) on a motorized treadmill. An 8% carbohydrate-electrolyte solution was consumed before and during exercise, either alone (CHO + PLA), or with 573 mg·kg-1 of a ketone monoester supplement (CHO + KME). Expired air, HR, and RPE were monitored during submaximal exercise. Serial venous blood samples were assayed for plasma glucose, lactate, and ß-hydroxybutyrate concentrations.